Preparation method of BaLiF3 ceramic material

Through mechanical grinding and high-temperature calcination, the energy barriers of BaLiF3 synthesis were successfully broken through, and efficient and low-cost BaLiF3 ceramic material preparation was achieved, solving the problems of strict reaction conditions, serious pollution and difficult to control purity in the existing methods, and it is suitable for industrial production.

CN119874369APending Publication Date: 2025-04-25SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510352401.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing BaLiF3 synthesis methods have problems such as strict reaction conditions, environmental pollution, difficult to control product purity, complex process and high cost, which are difficult to meet the needs of large-scale industrial production.

Method used

The preparation of BaLiF3 ceramic material is achieved by mixing the BaF2 powder with LiF powder and mechanically grinding to obtain a slurry, which is then dried and calcined at high temperature. This method uses mechanical energy to break through the energy barriers of BaLiF3 synthesis, simplify the process flow and reduce costs.

Benefits of technology

It realizes the efficient synthesis of BaLiF3, which has the characteristics of low cost, high purity and high conversion rate, and is suitable for industrial production, solving the problems of strict reaction conditions, serious pollution and difficult to control purity in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874369A_ABST
    Figure CN119874369A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a BaLiF3 ceramic material, which comprises the following steps: mixing BaF2 powder and LiF powder, and adding a grinding medium for mechanical grinding to obtain slurry; and drying the slurry, so as to obtain the BaLiF3 ceramic material. Mechanical energy is used as energy through mechanical grinding, the energy barrier of BaLiF3 synthesis is broken through, and the problems that in a traditional high-temperature solid-phase method, reaction conditions are strict, energy consumption is high, the environment is polluted, and the purity of products is difficult to control due to the fact that the products are prone to Li volatilization at high temperature and prone to being polluted by oxygen are solved. In addition, through mechanical energy preparation, the method has the characteristics of low cost, high efficiency, continuous production and the like, so that the defects that a hydrothermal synthesis method and a cosolvent method need to depend on special equipment, consume long time and are not beneficial to large-scale production are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic material preparation, and in particular relates to a method for preparing a perovskite-type composite fluoride BaLiF3 ceramic material. Background Art

[0002] With the deepening of the exploration of inorganic non-metallic materials, inorganic solid fluorides stand out among many materials with their excellent electron acceptor properties, high resistivity and significant anion conductivity, attracting widespread research interest. This compound not only exhibits strong ionicity, low phonon energy and limited electron cloud expansion effect, which makes it more advantageous than oxides and sulfides with similar structures in the fields of light energy storage, transmission, conversion and amplification, and thus attracts much attention as a functional material. As an emerging inorganic non-metallic material, perovskite-type composite fluorides have become a research hotspot due to their unique physical and chemical properties. In its chemical formula ABF3, the A position is usually occupied by rare earth or alkaline earth element ions, and the B position is occupied by transition element ions. Both the A and B positions show good ion substitution, which can introduce different metal ions while maintaining the stability of the crystal structure, providing an ideal platform for in-depth research on the catalyst surface and catalytic performance. Perovskite-type composite fluorides not only inherit the traditional advantages of fluorides, but also show extraordinary performance in piezoelectricity, ferromagnetism, thermal conductivity and electromagnetic properties. In addition, their high redox, hydrogenolysis, isomerization and electrocatalytic activities indicate that they have great application potential in key areas such as environmental protection and industrial catalysis. It is worth mentioning that because perovskite-type composite fluorides are easy to dope with various rare earth ions of different valence states, the precise design of material properties can be achieved by flexibly regulating the doping of rare earth elements, opening up new paths for innovation in laser technology and other fields.

[0003] In particular, BaLiF3 is the only experimentally confirmed ternary fluoride with an inverse cubic (cation inversion) perovskite structure, in which the low-valent Li + Occupies position B, and the high price Ba 2+ This unusual configuration gives BaLiF3 the characteristics of low phonon energy and wide bandgap, making it an ideal choice for laser technology, optical windows and lens manufacturing. In addition, its low dielectric constant and microwave loss characteristics also make it show potential application value in the field of microwave communications.

[0004] However, the road to synthesizing BaLiF3 is still not smooth. Although the traditional high-temperature solid-phase method can achieve synthesis, the harsh reaction conditions, environmental pollution and difficulty in controlling the purity of the product cannot be ignored; and the hydrothermal synthesis and co-solvent method require special equipment and are time-consuming. At present, the synthesis methods of BaLiF3 are mostly limited to small-scale laboratory preparation, facing challenges such as complex processes, high costs and low yields. It is difficult to meet the needs of large-scale industrial production, which in turn limits its commercialization process. Therefore, improving the synthesis conversion efficiency of BaLiF3, reducing preparation costs, and simplifying the process to achieve industrial production have become the key to promoting its industrialization and commercialization. Summary of the invention

[0005] The present invention aims to address the shortcomings of the above-mentioned existing BaLiF3 synthesis methods and provide a preparation method that is easy to industrialize and has low cost, high purity and high conversion rate.

[0006] Therefore, the present invention is implemented as follows: A preparation method of a BaLiF3 ceramic material comprises: mixing BaF2 powder and LiF powder, and performing mechanical grinding to obtain slurry; and drying the slurry to obtain the BaLiF3 ceramic material.

[0007] In the embodiment of the present invention, the mechanical grinding process requires the addition of grinding media.

[0008] In an embodiment of the present invention, the molar ratio between the BaF2 powder and the LiF powder is 1:(1 to 1.2).

[0009] In an embodiment of the present invention, the average particle size of the BaF2 powder is 0.1 μm to 20 μm, and the average particle size of the LiF powder is 0.1 μm to 20 μm.

[0010] In an embodiment of the present invention, the grinding medium includes a grinding particle and an auxiliary agent, wherein the shape of the grinding particle is selected from sphere, rod, cylinder, sheet, polygon or irregular geometry; the material of the grinding particle is selected from one or more combinations of zirconium oxide, aluminum oxide, silicon carbide, silicon nitride, stainless steel, agate, polyurethane, tungsten carbide or boron nitride; the auxiliary agent is one or more mixed solutions of water, ethanol and acetone.

[0011] In the implementation of the present invention, it further includes: performing high temperature calcination treatment on the BaLiF3 ceramic material.

[0012] In an embodiment of the present invention, the calcination temperature is 650° C. to 850° C., and the calcination time is 1 h to 12 h.

[0013] In an embodiment of the present invention, the high temperature calcination treatment is performed in one or more of a nitrogen, air, and oxygen environment.

[0014] In an embodiment of the present invention, the ratio of the mass of the grinding particle to the total mass of the BaF2 powder and the LiF powder is (2 to 15):1, and the ratio of the mass of the auxiliary agent to the total mass of the BaF2 powder and the LiF powder is (1 to 15):1.

[0015] In the implementation form of the present invention, the particle size of the grinding particle is 0.2mm to 40mm, during the mechanical grinding, the filling rate is 50% to 67%, the grinding speed is 30r / min to 2000r / min, and the grinding time is 0.5h to 100h.

[0016] In an embodiment of the present invention, after the high-temperature calcination treatment, the method further includes: adding the BaLiF3 ceramic material to a grinding medium for secondary mechanical grinding, followed by secondary drying, and then secondary high-temperature calcination treatment.

[0017] The technical solution proposed by the present invention has the following beneficial effects: The present invention can be said to be the first to generate perovskite-type fluorides by mechanical synthesis, and the BaLiF3 conversion rate can be adjusted by process parameters. Moreover, the BaLiF3 conversion rate can be further improved by further calcination. Therefore, if the required BaLiF3 conversion rate can be achieved by mechanical synthesis, the calcination treatment can be omitted. Furthermore, the present invention uses mechanical energy as energy through mechanical grinding to break through the energy barrier of BaLiF3 synthesis, and solves the problems of harsh reaction conditions, high energy consumption, environmental pollution, and the product is easy to cause Li volatilization at high temperature, and is susceptible to oxygen contamination, resulting in purity difficult to control. In addition, through mechanical energy preparation, it has the characteristics of low cost, high efficiency, and continuous production, thereby avoiding the defects of hydrothermal synthesis and co-solvent method that rely on special equipment and take a long time, which is not conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an X-ray diffraction result diagram, comparing the phase composition and crystal structure of the powders finally obtained in Examples 1 and 2; Figure 2 This is an X-ray diffraction technology result diagram, showing the phase composition and crystal structure of the powder finally obtained in Comparative Example 2; Figure 3 The X-ray diffraction results are compared to show the phase composition and crystal structure of the powders finally obtained in Examples 3 to 9; Figure 4 The X-ray diffraction results are compared to show the phase composition and crystal structure of the powders finally obtained from Examples 10 to 18; Figure 5 The X-ray diffraction results are compared with the phase composition and crystal structure of the powder finally obtained in Example 19; Figure 6 This is an X-ray diffraction technology result diagram, comparing the phase composition and crystal structure of the powders finally obtained in Examples 16, 20, and 21. DETAILED DESCRIPTION

[0019] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] The embodiment of the present invention provides a method for preparing a BaLiF3 ceramic material, which is a method for synthesizing BaLiF3 powder with low cost, high purity and high conversion rate.

[0022] First, BaF2 powder and LiF powder are mixed, and grinding media are added to perform mechanical grinding to obtain a slurry. Specifically, the average particle size of the BaF2 powder can be, but is not limited to, 0.1 μm to 20 μm, preferably 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm. μm; the average particle size of LiF powder can be, but is not limited to, 0.1 μm to 20 μm, preferably 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1 .5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm. Specifically, the molar ratio between BaF2 powder and LiF powder can be but is not limited to 1:(1 to 1.2), preferably 1:1, 1:1.002, 1:1.004, 1:1.006, 1:1.008, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1, or 1:1.2.

[0023] Mechanical grinding can be but not limited to conventional grinding means, preferably one or more of drum ball milling, planetary ball milling, sand milling, and vibration milling. The grinding media can include but are not limited to grinding particles and additives. The grinding particles can be but are not limited to one or more combinations of zirconium oxide, aluminum oxide, silicon carbide, silicon nitride, stainless steel, agate, polyurethane, tungsten carbide, or boron nitride.

[0024] The particle size of the grinding particles may be, but is not limited to, 0.2 mm to 40 mm, preferably 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm.

[0025] The ratio between the mass of the grinding grains and the total mass of the BaF2 powder and the LiF powder may be, but is not limited to, (2 to 15):1, preferably 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1. The auxiliary agent may be, but is not limited to, one or more of water, ethanol, and acetone. The ratio between the mass of the auxiliary agent and the total mass of the BaF2 powder and the LiF powder may be, but is not limited to, (1 to 15):1, preferably 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1. During mechanical grinding, the filling rate may be, but is not limited to, 50% to 67%, preferably 50%, 55%, 60%, 65%, or 67%; the grinding speed may be, but is not limited to, 30 r / min to 2000 r / min, preferably 30 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 90 r / min, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min The grinding time may be, but is not limited to, 0.5 h to 100 h, preferably 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, 60 h, 65 h, 70 h, 75 h, 80 h, 85 h, 90 h, 95 h, or 100 h.

[0026] Next, the slurry is dried to obtain a BaLiF3 ceramic material. The drying temperature may be, but is not limited to, 100°C to 150°C, preferably 100°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, or 150°C; the drying time may be, but is not limited to, 12h to 30h, preferably 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, or 30h.

[0027] In addition, in order to reduce the amount of BaF2 or LiF remaining in the BaLiF3 ceramic material, the obtained BaLiF3 ceramic material can be further subjected to a high-temperature calcination treatment. The high-temperature calcination treatment can be carried out in, but not limited to, conventional high-temperature treatment equipment, preferably in one or more of a tubular furnace and a muffle furnace. The high-temperature calcination treatment can be carried out in, but not limited to, one or more of a nitrogen, air, and oxygen environment. The calcination temperature may be, but not limited to, 650°C to 850°C, preferably 650°C, 700°C, 750°C, 800°C, or 850°C; the calcination time may be, but not limited to, 1h to 12h, preferably 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, or 12h.

[0028] In addition, in order to further reduce the amount of BaF2 or LiF remaining in the BaLiF3 ceramic material, the BaLiF3 ceramic material can be further added to a grinding medium for secondary mechanical grinding after the high-temperature calcination treatment, followed by secondary drying and then secondary high-temperature calcination treatment.

[0029] Secondary mechanical grinding may be but is not limited to conventional grinding means, preferably one or more of drum ball milling, planetary ball milling, sand milling, and vibration milling. The grinding media of secondary mechanical grinding may include but is not limited to grinding particles and additives. The shape of the grinding particles is selected from spherical, rod-shaped, cylindrical, flaky, polygonal or irregular geometric bodies; the grinding particles may be but are not limited to one or more of zirconium oxide grinding particles and aluminum oxide grinding particles; the particle size of the grinding particles may be but is not limited to 0.2 mm to 40 mm, preferably 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm. The ratio between the mass of the grinding particle and the mass of the BaLiF3 ceramic material may be, but is not limited to, (2 to 15):1, preferably 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1. The auxiliary agent may be, but is not limited to, one or more of water, ethanol, and acetone. The ratio between the mass of the auxiliary agent and the mass of the BaLiF3 ceramic material may be, but is not limited to, (1 to 15):1, preferably 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1.During secondary mechanical grinding, the filling rate may be, but not limited to, 50% to 67%, preferably 50%, 55%, 60%, 65%, or 67%; the grinding speed may be, but not limited to, 30 r / min to 2000 r / min, preferably 30 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 90 r / min, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min in, 1400r / min, 1500r / min, 1600r / min, 1700r / min, 1800r / min, 1900r / min, or 2000r / min; the grinding time may be, but is not limited to, 0.5h to 100h, preferably 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, 75h, 80h, 85h, 90h, 95h, or 100h.

[0030] The secondary drying temperature may be, but is not limited to, 100°C to 150°C, preferably 100°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, or 150°C; the secondary drying time may be, but is not limited to, 12h to 30h, preferably 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, or 30h.

[0031] The secondary high temperature calcination treatment can be carried out in, but not limited to, conventional high temperature treatment equipment, preferably in one or more of a tube furnace and a muffle furnace. The secondary high temperature calcination treatment can be carried out in, but not limited to, one or more of a nitrogen, air, and oxygen environment. The secondary calcination temperature can be, but not limited to, 650°C to 850°C, preferably 650°C, 700°C, 750°C, 800°C, or 850°C; the secondary calcination time can be, but not limited to, 1h to 12h, preferably 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, or 12h.

[0032] The preferred embodiment of the present invention provides a method for preparing a BaLiF3 ceramic material, which can be implemented according to the following steps: (1) The BaF2 and LiF raw materials are subjected to separate ball milling, screening, material selection and other steps to obtain raw materials with a desired particle size range; (2) Add BaF2 and LiF raw materials of the required particle size range into a ball mill or grinder in a certain proportion, and then add zirconium oxide balls of a certain size and grinding media such as water, ethanol or acetone for wet grinding, and control the ball-to-material mass ratio, ball mill filling rate, ball mill speed and ball milling time. During this period, the slurry viscosity must be appropriate: if the slurry is too thick, the raw materials will agglomerate and cannot be dispersed evenly; if the slurry is too thin, the zirconium oxide grinding wheel will not be able to rotate the slurry and it is easy to cause the grinding wheel to wear and cause impurities to enter, and it will also cause the raw materials to stratify during drying; in addition, the appropriate speed must be adjusted to enable the grinding wheel to break the powder; (3) The milled slurry is taken out, dried, sieved, and mixed powder is obtained; (4) The mixed powder is further calcined in a tube furnace at a certain temperature, and high-purity nitrogen or oxygen or no gas is introduced during the calcination process; (5) The calcined powder can be further ball-milled to reduce its particle size as needed.

[0033] The present invention is illustrated by the following examples: Example 1 BaF2 (purity 99.99%, particle size 0.3µm to 1µm) and LiF (purity 99.99%, particle size 0.3µm to 2µm) were used as the initial raw materials, and were weighed in a 1:1 molar ratio and added to a polypropylene ball mill. Zirconia grinding particles and ethanol were added in a mass ratio of 1:3 and 1:1, respectively. The filling rate of the ball mill was 50%, the average particle size of the grinding particles was 2mm, and the mixture was ball milled on a drum ball mill at a grinding speed of 60r / min for 24h.

[0034] The ball-milled slurry was taken out and poured into a porcelain plate, placed in an oven at 120°C for 24 hours for drying, and then sieved with a 100-mesh sieve to obtain a powder.

[0035] Example 2 Same as Example 1, except that ethanol was replaced with deionized water.

[0036] Example 3 Same as Example 2, except that BaF2 and LiF are in a molar ratio of 1:1.002.

[0037] Example 4 Same as Example 2, except that BaF2 and LiF are in a molar ratio of 1:1.004.

[0038] Example 5 Same as Example 2, except that BaF2 and LiF are in a molar ratio of 1:1.006.

[0039] Example 6 Same as Example 2, except that BaF2 and LiF are in a molar ratio of 1:1.008.

[0040] Example 7 Same as Example 2, except that BaF2 and LiF are in a molar ratio of 1:1.01.

[0041] Example 8 BaF2 (purity 99.99%, particle size 0.3µm to 1µm) and LiF (purity 99.99%, particle size 0.3µm to 2µm) were used as the initial raw materials, and were weighed in a 1:1.006 molar ratio and added to a sand mill. Zirconia grinding stones and deionized water were added in a mass ratio of 1:3 and 1:1, respectively. The average particle size of the grinding stones was 0.4mm, and the mixture was sand milled at a grinding speed of 1200r / min for 0.5h.

[0042] The ball-milled slurry was taken out and poured into a porcelain plate, placed in an oven at 120°C for 24 hours for drying, and then sieved with a 100-mesh sieve to obtain a powder.

[0043] Example 9 Same as Example 5, except that LiF (purity 99.99%, particle size 0.3µm to 2µm) was replaced with LiF (purity 99.99%, particle size 7.6µm to 17µm).

[0044] Example 10 The same as Example 2, except that the obtained powder was calcined at 700° C. for 2 h in a tubular furnace with high-purity nitrogen.

[0045] Embodiment 11 BaF2 (purity 99.99%, particle size 0.3µm to 1µm) and LiF (purity 99.99%, particle size 0.3µm to 2µm) were used as the initial raw materials, and were weighed in a 1:1 molar ratio and added to a polypropylene ball mill. Zirconia grinding particles and deionized water were added in a mass ratio of 1:3 and 1:1, respectively. The filling rate of the ball mill was 50%, the average particle size of the grinding particles was 2mm, and the mixture was ball milled on a drum ball mill at a grinding speed of 60r / min for 24h.

[0046] The ball-milled slurry was taken out and poured into a porcelain plate, placed in an oven at 120°C for 24 hours for drying, and then sieved with a 100-mesh screen to obtain a powder. Next, the obtained powder was calcined at 700°C for 2 hours in a tubular furnace with high-purity nitrogen.

[0047] The calcined powder was added to a polypropylene ball mill, and zirconium oxide grinding particles and deionized water were added in a mass ratio of 1:3 and 1:1, respectively. The filling rate of the ball mill was 50%, the average particle size of the grinding particles was 2 mm, and the mixture was ball milled on a drum ball mill at a grinding speed of 60 r / min for 24 h.

[0048] The ball-milled slurry was taken out and poured into a porcelain plate, placed in an oven at 120°C for 24 hours for drying, and then sieved with a 100-mesh screen to obtain a powder. Next, the powder was calcined at 700°C for 2 hours in a tubular furnace with high-purity nitrogen.

[0049] Example 12 Same as Example 10, except the calcination temperature was 750°C.

[0050] Embodiment 13 Same as Example 10, except the calcination temperature was 800°C.

[0051] Embodiment 14 The same as Example 3, except that the obtained powder was calcined at 750° C. for 2 h in a tubular furnace with high-purity nitrogen.

[0052] Embodiment 15 The same as Example 4, except that the obtained powder was calcined at 750° C. for 2 h in a tubular furnace with high-purity nitrogen.

[0053] Example 16 The same as Example 5, except that the obtained powder was calcined at 750° C. for 2 h in a tubular furnace with high-purity nitrogen.

[0054] Embodiment 17 The same as Example 6, except that the obtained powder was calcined at 750° C. for 2 h in a tubular furnace with high-purity nitrogen.

[0055] Embodiment 18 The same as Example 7, except that the obtained powder was calcined at 750° C. for 2 h in a tubular furnace with high-purity nitrogen.

[0056] Embodiment 19 The same as Example 2, except that BaF2 and LiF are in a molar ratio of 1:1.2, and the obtained powder is calcined at 750°C for 2h in a tubular furnace with high-purity nitrogen.

[0057] Embodiment 20 Same as Example 16, except that the nitrogen gas was replaced by air.

[0058] Embodiment 21 Same as Example 16, except that the nitrogen was replaced by oxygen.

[0059] Comparative Example 1 BaF2 (purity 99.99%, particle size 0.3µm to 1µm) and LiF (purity 99.99%, particle size 0.3µm to 2µm) were used as the initial raw materials, which were weighed in a 1:1 molar ratio and poured into an agate mortar respectively, and then anhydrous ethanol was slowly added in a 1:1 mass ratio for thorough grinding.

[0060] The ground slurry was taken out and poured into a porcelain plate, placed in a 120°C oven for drying, and then sieved with a 100-mesh sieve to obtain a powder.

[0061] Comparative Example 2 The same as comparative example 1, except that the obtained powder is passed through high-purity nitrogen in a tube furnace.

[0062] X-ray diffraction test The phase composition and crystal structure of the material are characterized by X-ray diffraction (XRD). The atoms in the crystal material can form a grating for X-ray diffraction due to their periodic arrangement. X-rays diffract through the crystal grating, and the superposition of diffraction waves increases the intensity of the rays in some directions and weakens them in other directions. The crystal structure of the material can be determined by analyzing the diffraction pattern. The formula can be used to calculate the interplanar spacing of the crystal, and then the crystal structure of the material can be analyzed. Using analysis software such as Jade6, by comparing the XRD results of the sample with the diffraction peak position and intensity of the material standard card, the phase composition and crystal structure of the sample can be qualitatively determined, and the phase content can be determined by refinement. In order to eliminate the residual stress and preferred grain orientation that may exist in the sample, powder samples are uniformly tested.

[0063] Scanning electron microscope test A scanning electron microscope (SEM) was used to observe the microscopic morphology of the samples, and an energy dispersive spectrometer (EDS) was used for elemental analysis.

[0064] The XRD powder diffraction results of Examples 1 and 2 are as follows: Figure 1As shown, it can be observed that the powders of the two examples have diffraction peaks that completely match the BaLiF3 (Pm-3m, PDF#18-0715) standard card and have a simple cubic perovskite structure. The partial enlarged image on the right shows that Example 1, which was ball-milled with ethanol, has more residual BaF2 (Fm-3m, PDF#85-1342) and LiF (Fm-3m, PDF#04-0857) (~28wt%, BaLiF3 conversion rate is ~72%), while Example 2, which was ball-milled with deionized water, only has a trace amount of cubic phase BaF2 (content ~1wt%, BaLiF3 conversion rate is 99%). In addition, it can be seen from Comparative Example 1 that BaLiF3 cannot be synthesized by simply grinding the raw materials in a mortar; as shown in FIG. Figure 2 As shown, from Comparative Example 2, it can be seen that BaLiF3 must be further calcined at high temperature to synthesize (the conversion rate of BaLiF3 is ~95%). The above results show that the synthesis of BaLiF3 is successfully achieved by the traditional drum ball milling method, which indicates that the mechanical energy applied by this method is sufficient to cross the energy barrier of BaLiF3 synthesis. It was found that the use of deionized water as a grinding medium can significantly improve the conversion rate of the synthesis compared with ethanol. During the grinding process, the frequent friction and fierce impact between the raw material particles not only induce local plastic deformation of the raw material, but also form a rich defect structure on its surface. This change not only reshapes the microstructure of the raw material, making it more conducive to the contact and mixing of the reactants, but also greatly improves the chemical reaction activity of the surface by increasing surface defects. It is worth noting that the energy release at the moment of impact causes the temperature at the impact point to rise sharply, providing additional energy incentives for the occurrence of chemical reactions. The synergy of this series of physical and chemical effects jointly promotes the efficient synthesis of BaLiF3 during the grinding process.

[0065] The XRD powder diffraction results of the powders with different initial ratios of BaF2 to LiF (BaF2:LiF = 1:1 to 1.01) after ball milling with deionized water for 24 hours are as follows: Figure 3As shown. It can be observed that the main phase diffraction peaks of all components can be completely matched with the BaLiF3 standard card, and no LiF residue is observed within the XRD detection limit, which may be due to the low LiF content and weak reflection intensity (small Li atom scattering factor). After 24 hours of ball milling, the degree of conversion of LiF and BaF2 to BaLiF3 is close to 100%, and the residual BaF2 content is less than 1wt%, and it does not change much with the increase of LiF excess. The sand milling of Example 8 provides higher mechanical energy through a higher rotation speed to further improve the conversion rate, and no LiF and BaF2 residue is observed within the XRD detection limit. In addition, the use of LiF raw materials with larger particle size in Example 9 will reduce the conversion rate, and more LiF and BaF2 will remain (~7.2wt%, BaLiF3 conversion rate is 92.8%), which shows that in addition to the grinding media and ball milling energy, the initial particle size of the raw material will also affect the conversion rate, and the smaller the particle size, the higher the conversion rate.

[0066] Examples 10 to 18 are obtained by calcining the powder at high temperature in a nitrogen atmosphere for a certain period of time. The XRD powder diffraction results are as follows: Figure 4 As shown. The results show that high-temperature calcination treatment can also further promote the synthesis of BaLiF3. After calcination at 750℃ for 2h, it can be observed that the components in the range of BaF2:LiF=1:1.002 to 1.01 all present a single phase of BaLiF3, and no residual LiF and BaF2 are observed within the XRD detection limit. For the component of BaF2:LiF=1:1, due to the water dissolution loss of LiF during the ball milling process, residual BaF2 can still be observed regardless of multiple synthesis at 700℃ / 2h (calcination after secondary ball milling) or calcination at 800℃ for 2h. This shows that the excessive addition of 0.2mol% LiF is sufficient to compensate for its water dissolution loss and obtain single-phase BaLiF3. The XRD results of Example 19 ( Figure 5 ) shows that too much LiF will remain in the synthesized BaLiF3 even after high-temperature calcination, which means that the synthesis of BaLiF3 is within the appropriate raw material ratio range.

[0067] The same batch of mechanically synthesized powders were further calcined at high temperatures under different atmospheres. Although the XRD results ( Figure 6 ) have no significant difference, both are single-phase BaLiF3, but the EDS results (shown in Table 1) show that high-temperature calcination in an oxygen-containing atmosphere will cause the synthesized BaLiF3 to be contaminated by oxygen.

[0068]

[0069] The present invention uses conventional ball milling or sand milling technology and mechanical energy as the driving core to successfully break through the energy barrier of BaLiF3 synthesis and realize the effective synthesis of BaLiF3. In the process of in-depth research, multiple key factors such as the ratio of LiF to BaF2, the selection of grinding media, the application of ball milling energy, the control of sintering atmosphere and the size of raw material particle size are systematically examined to determine the specific effects on the phase composition and conversion rate of BaLiF3. Through this series of optimization measures, the present invention successfully solves the bottleneck problems existing in traditional synthesis methods, such as harsh reaction conditions, serious environmental pollution, difficult to control product purity and long preparation time. More importantly, the implementation of the present invention significantly reduces the preparation cost, greatly simplifies the process flow, and shows broad prospects for industrial application.

[0070] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0071] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined by the scope of the claims.

Claims

1. A method for preparing a BaLiF3 ceramic material, characterized in that: include: BaF2 powder and LiF powder are mixed, and grinding media are added for mechanical grinding to obtain slurry; wherein the molar ratio between the BaF2 powder and the LiF powder is 1: (1 to 1.2), the average particle size of the BaF2 powder is 0.1 μm to 20 μm, the average particle size of the LiF powder is 0.1 μm to 20 μm, the grinding media includes a grinder and an auxiliary agent, the material of the grinder is selected from one or more combinations of zirconium oxide, aluminum oxide, silicon carbide, silicon nitride, stainless steel, agate, polyurethane, tungsten carbide, and boron nitride, the auxiliary agent is one or more mixed solutions of water, ethanol, and acetone, the particle size of the grinder is 0.2 mm to 40 mm, and during the mechanical grinding, the filling rate is 50% to 67%, the grinding speed is 30 r / min to 2000 r / min, and the grinding time is 0.5 h to 100 h; as well as The slurry is dried to obtain BaLiF3 ceramic material.

2. The method for preparing BaLiF3 ceramic material according to claim 1, characterized in that: Also includes: The BaLiF3 ceramic material is subjected to a calcination treatment.

3. The method for preparing BaLiF3 ceramic material according to claim 1, characterized in that: The shape of the grinding element is selected from sphere, rod, cylinder, sheet, polygon or irregular geometry.

4. The method for preparing BaLiF3 ceramic material according to claim 2, characterized in that: The calcination temperature is 650° C. to 850° C., and the calcination time is 1 hour to 12 hours.

5. The method for preparing BaLiF3 ceramic material according to claim 2, characterized in that: The calcination treatment is performed in one or more of nitrogen, air and oxygen environments.

6. The method for preparing BaLiF3 ceramic material according to claim 1, characterized in that: The ratio of the mass of the grinding particle to the total mass of the BaF2 powder and the LiF powder is (2 to 15):1, and the ratio of the mass of the auxiliary agent to the total mass of the BaF2 powder and the LiF powder is (1 to 15):

1.

7. The method for preparing BaLiF3 ceramic material according to claim 2, characterized in that: After the calcination treatment, the method further includes: adding the BaLiF3 ceramic material to a grinding medium for secondary mechanical grinding, followed by secondary drying, and then secondary calcination treatment.

Citation Information

Patent Citations

  • Technology of preparing nanometer composite oxide by mechanical grinding

    CN1868967A